2017
DOI: 10.5194/isprs-archives-xlii-2-w6-85-2017
|View full text |Cite
|
Sign up to set email alerts
|

Uav Cameras: Overview and Geometric Calibration Benchmark

Abstract: ABSTRACT:Different UAV platforms and sensors are used in mapping already, many of them equipped with (sometimes) modified cameras as known from the consumer market. Even though these systems normally fulfil their requested mapping accuracy, the question arises, which system performs best? This asks for a benchmark, to check selected UAV based camera systems in well-defined, reproducible environments. Such benchmark is tried within this work here. Nine different cameras used on UAV platforms, representing typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 2 publications
0
48
0
1
Order By: Relevance
“…Hereafter the results given in this paper are connected to the work of Cramer et al (2017a). As part of their investigation different UAV camera systems have been calibrated with airborne image data in a calibration field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hereafter the results given in this paper are connected to the work of Cramer et al (2017a). As part of their investigation different UAV camera systems have been calibrated with airborne image data in a calibration field.…”
Section: Discussionmentioning
confidence: 99%
“…Another topic is a) to combine the experiment results under static / laboratory conditions with radiometrical correction parameters (PRNU / DSNU) to provide more fundamental information and b) to verify radiometrical and geometrical quality characteristics presented by Cramer et al (2017a) under dynamic / operating conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camera calibration in GCP-controlled UAV blocks is discussed by several papers [10,37,45]. While pre-calibration is recommended in principle, the stability of camera parameters is questionable: Cramer et al [45] found less accurate results using laboratory calibration parameters, while Harwin et al [10] found on-the-job self-calibration just as accurate.…”
Section: Camera Calibrationmentioning
confidence: 99%
“…While pre-calibration is recommended in principle, the stability of camera parameters is questionable: Cramer et al [45] found less accurate results using laboratory calibration parameters, while Harwin et al [10] found on-the-job self-calibration just as accurate. Self-calibration is likely to be the Remote Sens.…”
Section: Camera Calibrationmentioning
confidence: 99%